The Reform of the Higher Education Public Administration Programs in the Context of Public Administration Reform in Romania - Călin HINŢEA; David RINGSMUTH; Cristina MORA (Transylvanian Review of Administrative Sciences, 2006)
Public administration reform is an issue that was often been mentioned within public debates in Romania since1989. Unfortunately, a public debate has seldom been represented by a cogent analysis of the reforms undertaken in the field of public administration. Romania, like other European countries, has been strongly influenced by the legalistic approach of the public administration field; the reform has been often equated with passing of new legislation and regulations. Consequently, year-by-year, EU reports on the development of public administration have highlighted implementation issues (the lack of implementation capacity for legislation and public policy being a constant failure discussed in these reports). The personnel is one of the problems which public administration reform has to deal with. The quality of the human resources is crucial. In many cases, modernization of public administration has been strongly encouraged by the appearance of a new generation of public servants who are results – oriented not procedures/process – oriented, and who have been trained differently. This paper analyzes the role that public administration programs of Romanian universities could play in the administrative reform process.